(3cJGH CWYeI GdeQVis - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf EYde Cf CMO GdYdhe GdJi jfJaY HgG GdfGS gh Yde GdWH hgh ef LedI GdYdhe GdSjGSjI s
(3BNQgG (B:s
(3hcd MGd ef MGdGJ GdHOf hbJ ef ChbGJ GdSfI hSf ef GdCSfGf hYfO Ydjg cd NdW ef GdCNdGW hGdMeO ddg QH GdYGdejf JeJ GdcJGH CWYeI GdeQVi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCSJGP (B- (3YHO GdeMSf Hf MeO GdYHGO s
Keywords: (3GdWHs